1992
DOI: 10.1002/cne.903250409
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of substance P‐ and cholecystokinin‐like immunoreactivity during regeneration of the neural complex in the ascidian Ciona intestinalis

Abstract: The neural ganglion of ascidians exhibits a novel and rapid pattern of regeneration whereby within approximately 28-35 days of total ablation an entirely new neural complex is formed. In normal adults, neuronal cell bodies expressing substance P- (SP-Li), neurokinin A-(NKA-Li), CCK/gastrin- (CCK-Li), and insulin-like immunoreactivity exhibit a clearly defined pattern of localization in the cortical rind of the ganglion with characteristic long processes arising from the perikarya running throughout the neuropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…In particular, the positive reaction for substance P in granule cells and its co-localization with TGF-β in their granules seem to strongly suggest a possible glial function for the granule cells and indicate primary involvement of this neuropeptide (or at least a substance-P-like molecule) as an essential neurotrophic factor that acts synergistically with other molecules in the processes of maintenance, repair, and growth of the associated nerve components, whose early expression might be a key factor in neural regeneration. Furthermore, its presence outside the nervous system at the level of blastemal cells actively involved in cell proliferation suggests that substance P could be released specifically to play a wider role as an important regulatory factor stimulating active growth and cell division (Smith et al 1995) and could be implicated in regenerative phenomena as described in other animal models, vertebrate or invertebrate (Zachary et al 1987;Baguña et al 1989;Thorndyke 1989;Globus and Alles 1990;Bollner et al 1992Bollner et al , 1993.…”
Section: Substance Pmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, the positive reaction for substance P in granule cells and its co-localization with TGF-β in their granules seem to strongly suggest a possible glial function for the granule cells and indicate primary involvement of this neuropeptide (or at least a substance-P-like molecule) as an essential neurotrophic factor that acts synergistically with other molecules in the processes of maintenance, repair, and growth of the associated nerve components, whose early expression might be a key factor in neural regeneration. Furthermore, its presence outside the nervous system at the level of blastemal cells actively involved in cell proliferation suggests that substance P could be released specifically to play a wider role as an important regulatory factor stimulating active growth and cell division (Smith et al 1995) and could be implicated in regenerative phenomena as described in other animal models, vertebrate or invertebrate (Zachary et al 1987;Baguña et al 1989;Thorndyke 1989;Globus and Alles 1990;Bollner et al 1992Bollner et al , 1993.…”
Section: Substance Pmentioning
confidence: 96%
“…It has further been demonstrated by means of invitro and in-vivo experiments carried out mostly in mammals that this neuropeptide can induce degranulation of mast cells, promote chemotaxis of neutrophilic leucocytes, stimulate release of lysosomal enzymes from polymorphonuclear leucocytes, increase phagocytosis from neutrophils and macrophages, and stimulate lymphocyte proliferation (Bar-Shavit et al 1980;Nilsson et al 1985;Payan 1985;Hartung et al 1986). Substance-P-like peptides have been detected in the nervous system of many invertebrates and appear to be involved specifically in developmental and regeneration processes as mitogenic factors (Zachary et al 1987;Baguna et al 1989;Thorndyke 1989;Bollner et al 1992Bollner et al , 1993. In echinoderms the available data on the presence and distribution of substance P are largely restricted to crinoids (Candia Carnevali et al 1998b, and evidence has been obtained entirely by means of immunocytochemical methods that employed a rabbit antibody raised against the mammalian peptide, so the limitation this imposes must be taken into account.…”
Section: Substance Pmentioning
confidence: 99%
“…Bollner et al have shown that the expression patterns of certain transmitters (i.e. GNRH, 5-HT, SP) are recovered in the new cerebral ganglion, which, however, remains smaller than the original [23], [24].…”
Section: Introductionmentioning
confidence: 98%
“…Regeneration is probably more limited in solitary ascidians, such as Ciona intestinalis , in which distal body parts can be replaced from proximal parts, as long as the latter contain a portion of the branchial sac (Hirschler, 1914; Jeffery, 2015a). In Ciona , the oral siphon (OS), a muscular tube leading into the mucus-forming pharynx, and the neural complex, which includes the brain and the associated neural gland, are able to regenerate with complete fidelity within about a month after their removal (Sutton, 1953; Whittaker, 1975; Bollner, et al, 1992; 1993; 1995; Dahlberg et al, 2009; Auger et al, 2010). The OS pigment organs (OPO), which are sensory receptors rimming the siphon opening (Dilly and Wolken, 1973), and the circular muscle fibers lying immediately below them, reappear more rapidly, within about 5–10 days after amputation (Auger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%